2021
DOI: 10.1002/1438-390x.12092
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and comparative demographics in sympatric populations of the round‐leaved orchids Platanthera macrophylla and P. orbiculata

Abstract: Orchids (Orchidaceae) are a family of flowering plants with a high proportion of threatened taxa making them an important focus of plant conservation.Orchid conservation efforts are most effective when informed by reliable demographic research. We utilized transition matrix models to examine the population dynamics and demography within sympatric populations of a species pair of terrestrial round-leaved orchids, Platanthera macrophylla and P. orbiculata. The models were parameterized from a large data set span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Identifying co‐evolutionary selective pressures among plants and insects is important but challenging. Botanists and entomologists often use different approaches – botanists may focus on the impacts of pollination on reproductive success (Inoue, 1986 ; Vojtkó et al., 2015 ), gene flow (Wallace & Bowles, 2023 ), and population dynamics (Berry & Cleavitt, 2021 ), whereas entomologists may focus on the energetics of obtaining a reward or trying to fly with a pollen load, synchrony among plant and pollinator phenology, or attempts to cheat the system through nectar robbing (Feuerbacher et al., 2003 ; Fox et al., 2015 ; Mountcastle et al., 2015 ; Slominski & Burkle, 2021 ). Efforts to study both the behavior and energetic needs of pollinators and the subsequent consequences on reproductive output in plants, simultaneously are not always common.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying co‐evolutionary selective pressures among plants and insects is important but challenging. Botanists and entomologists often use different approaches – botanists may focus on the impacts of pollination on reproductive success (Inoue, 1986 ; Vojtkó et al., 2015 ), gene flow (Wallace & Bowles, 2023 ), and population dynamics (Berry & Cleavitt, 2021 ), whereas entomologists may focus on the energetics of obtaining a reward or trying to fly with a pollen load, synchrony among plant and pollinator phenology, or attempts to cheat the system through nectar robbing (Feuerbacher et al., 2003 ; Fox et al., 2015 ; Mountcastle et al., 2015 ; Slominski & Burkle, 2021 ). Efforts to study both the behavior and energetic needs of pollinators and the subsequent consequences on reproductive output in plants, simultaneously are not always common.…”
Section: Discussionmentioning
confidence: 99%
“…Platanthera macrophylla has higher fecundity but flowers less frequently than P. orbiculata , which has both higher transition from vegetative to flowering adults and more flowering adults that remain flowering. The LTRE showed that variation in annual population growth rates were most affected by adult survival and fruit set for both species, although P. macrophylla was more sensitive to variation in protocorm transition (Berry & Cleavitt, 2021).…”
Section: Cover Page Photos and Figuresmentioning
confidence: 99%